Group Creativity Training for Children: Lessons Learned from Two Award‐Winning Teams. (9th February 2015) - Shin, Namin; Jang, Yeon‐Ju
Abstract: The development of group creativity can be challenging for both young students and their teachers. This study examined the processes and learning outcomes of group creativity training from the perspectives of elementary school students and teachers while identifying critical factors that contributed to the success of the training. Data were collected from two Korean elementary school teams that won the gold (1st) and a special medal at the 2011 Destination Imagination global competition. Both individual and group interviews were carried out with 13 students and two teachers to investigate their perspectives of group creativity training. The analysis of the interview data revealed three major factors and subthemes: group dynamics (conflict and play), individual characteristics of the students (personality and motivation), and teachers' roles (training strategies, training style, and commitment). In addition, a semi‐longitudinal survey conducted a year after the interviews examined nine skill or competency domains (self‐management, creativity, leadership, interpersonal relationship, patience, cooperation, information processing, communication, and presentation) to evaluate effects of the group creativity training on student learning. Synthesizing the analyses, we addressed the following three topics that arose from the discussions: the Safe Nest Effect, teachers' training style, and multiple learning experiences derived from group creativity training.